Burden of Undiagnosed HIV Cases & Associated Stigma Prevalent In Health Care System Including Mortuary - Singh, Dr. Raghvendra; Verma, Dr. Anoop Kumar; Venkatesh, Dr. Vimala; Kumar, Dr. Navneet; Kumari, Dr. Reema; Dr. Mousami Singh, Dr. Raja Rupani, Dr. Sangeeta Kumar, (International Journal of Innovative Research in Medical Science, 2017)
Prevalence of Undiagnosed HIV cases and associated stigma is a great blow to our health care system. Along with posing a great risk to health care worker, this may also lead to reluctant behaviour of health care personnel towards patient. Problem gets more aggravated in context to handling of forensic cases because there is a good deal of concern over the likelihood of becoming infected with HIV by performing necropsies on undiagnosed HIV positive corpses. These cases usually jeopardize the effort taken to combat HIV/AIDS and make health care personnel more anxious towards performing their duty.